Causal Effect of MMP-1 (Matrix Metalloproteinase-1), MMP-8, and MMP-12 Levels on Ischemic Stroke: A Mendelian Randomization Study. Issue 7 (27th April 2021) - Cárcel-Márquez, Jara; Cullell, Natalia; Muiño, Elena; Gallego-Fabrega, Cristina; Lledós, Miquel; Ibañez, Laura; Krupinski, Jerzy; Montaner, Joan; Cruchaga, Carlos; Lee, Jin-Moo; Gill, Dipender; Paré, Guillaume; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: MMP (matrix metalloproteinase) levels have been widely associated with ischemic stroke risk and poststroke outcome. However, their role as a risk factor or as a subeffect because of ischemia is uncertain. Methods: We performed a literature search of genome-wide studies that evaluate serum/plasma levels of MMPs. We used a 2-sample Mendelian randomization approach to evaluate the causality of MMP levels on ischemic stroke risk or poststroke outcome, using 2 cohorts: MEGASTROKE (n=440 328) and GODs (n=1791). Results: Genome-wide association studies of MMP-1, MMP-8, and MMP-12 plasma/serum levels were evaluated. A significant association, which was also robust in the sensitivity analysis, was found with all ischemic strokes: MMP-12 (odds ratio=0.90 [95% CI, 0.86–0.94]; q value=7.43×10 − 5 ), and with subtypes of stroke, large-artery atherosclerosis: MMP-1 (odds ratio=0.95 [95% CI, 0.92–0.98]; q value=0.01) and MMP-12 (odds ratio=0.71 [95% CI, 0.65–0.77]; q value=5.11×10 − 14 ); small-vessel occlusion: MMP-8 (odds ratio=1.24 [95% CI, 1.06–1.45]; q value=0.03). No associations were found in relation to stroke outcome. Conclusions: Our study suggests a causal link between lower serum levels of MMP-12 and the risk of ischemic stroke, lower serum levels of MMP-1 and MMP-12 and the risk of large-artery stroke and higher serum levels of MMP-8 and the risk of lacunar stroke.